(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
هدف هذا البحث الى اجراء التوصيف الجزيئي ودراسة درجة التباين والقرابة الوراثية بين عدد من الطرز المحلية من الورد الدمشقي Rosa damascena باستخدام تقنية RAPD المعتمدة على المكاثرة العشوائية لقطع الدنا المتباينة. تم استخلاص الـدنا DNA الكلي من العينات، وأجري التفاعل التسلسلي البوليمرازي (PCR) مع 24 بادئة Primer من شركة VBC-Genomics. أظهرت 19 بادئة من أصل 24 بادئة منها كفاءة في كشف تباينات بين الطرز المدروسة، إذ أظهرت هذه البادئات 210 حزمة كلية متباينة بنسبة 87.6 %. وفي طرز الورد الدمشقي، بلغ العدد الكلي للحزم 143حزمة وكانت نسبة التباين الوراثي 62.9%. أمكن تحديد بادئات تسمح بتمييز أنواع الورد الثلاثة المدروسة، وتحديد بادئات أخرى لتمييز طرز الورد الدمشقي المتباينة و المجموعة من مناطق مختلفة. أظهرت النتائج كفاءة التقنية المستخدمة في إظهار فروقات واضحة بين الطرز المدروسة المأخوذة من مناطق مختلفة، ومكنت من رسم شجرة القرابة لها. The aim of the present study was the molecular characterization and the evaluation of variability and genetic relationship of some Rosa damascena genotypes using PCR-based RAPD technique. Total DNA was isolated from young green leaves of samples followed by running PCR reactions using 24 random primers. Polymorphism of investigated genotypes was observed in reactions with 19 tested RAPD primes which gave repeatable polymorphic products producing a total of 210 bands. The level of polymorphism amounted to 87.6% in the whole genotypes studied, while it amounted to 62.9% in case of R. damascena with a total of 143 bands. Results proved that RAPD was an efficient technique in discriminating between the studied genotypes collected from different areas and representing the genetic relationships in the form of dendrogramm.